2020
DOI: 10.3221/igf-esis.53.26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatment on the fatigue strength of additive manufactured Ti6Al4V alloy

Abstract: Different alloys can be used for Additive Manufacturing (AM) with good structural strength. Among the titanium alloys, Ti6Al4V is the most used, especially for aerospace applications. There have been many analyses of the mechanical properties of additive manufactured Ti-6Al-4V with very good static strength results in general. However, there are still some difficulties to get fatigue properties close enough to the ones of specimens manufactured using traditional processes Considering the high effect of surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Thus, it is necessary to remove surface defects and/or reduce surface roughness using other methods such as machining [25]. It has been reported that the fatigue life of PBF/ Ti6Al4V decreases with an increase in the maximum surface roughness [26], and the surface roughness affects the fatigue strength of PBF/ Ti6Al4V [27][28][29][30][31], thus a reduction in the surface roughness of PBF/ Ti6Al4V is required to improve the fatigue properties. To reduce surface roughness of PBF metals, mechanical surface finishing [32], ultrasonic cavitation abrasive finishing [33], chemical etching [34], ultrasonic shot peening [35], cavitation abrasive surface finishing [36,37], hydrodynamic cavitation abrasive finishing [38,39], barreling [40], and linishing [40] have been proposed, and the improvement of fatigue strength of PBF/Ti6Al4V was demonstrated [32,36,37,40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is necessary to remove surface defects and/or reduce surface roughness using other methods such as machining [25]. It has been reported that the fatigue life of PBF/ Ti6Al4V decreases with an increase in the maximum surface roughness [26], and the surface roughness affects the fatigue strength of PBF/ Ti6Al4V [27][28][29][30][31], thus a reduction in the surface roughness of PBF/ Ti6Al4V is required to improve the fatigue properties. To reduce surface roughness of PBF metals, mechanical surface finishing [32], ultrasonic cavitation abrasive finishing [33], chemical etching [34], ultrasonic shot peening [35], cavitation abrasive surface finishing [36,37], hydrodynamic cavitation abrasive finishing [38,39], barreling [40], and linishing [40] have been proposed, and the improvement of fatigue strength of PBF/Ti6Al4V was demonstrated [32,36,37,40].…”
Section: Introductionmentioning
confidence: 99%
“…Further, tailoring the residual stress profile of PBF/Ti6Al4V using LP has been proposed [43]. Because the fatigue strength of PBF/Ti6Al4V is affected by surface roughness and residual stress [28,29,44], the improvement in the fatigue strength of PBF/Ti6Al4V by mechanical surface treatment has been investigated in terms of the surface roughness and compressive residual stress. Microstructural changes owing to mechanical surface modifications have also been considered.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that under a stress amplitude equal to about 300 MPa, the fatigue life could increase up to about 110%. Navarro et al 9 analyzed the effect produced by some surface treatments on the fatigue properties of an additive manufactured Ti‐6Al‐4V titanium alloy. More precisely, after annealing and sand blasting, four treatments were used, that is, SP, SP plus chemical‐assisted surface enhancement (CASE), laser shock peening, and hot isostatic pressing (HIP), having such treatments mainly three effects on the material, consisting in surface roughness modification, inducing compressive residual stresses and pore size decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different surface treatments, shot peening has been the most extended method applied to AM Ti6Al4V parts. Although it is not very suitable for inaccessible surfaces, it improves fatigue strength and fatigue life by reducing roughness and by introducing compressive residual stresses which prevent the initiation of fatigue failure [21]. Other variants of shot peening such as laser peening and cavitation peening act in a similar way but with enhanced fatigue properties [22].…”
Section: Introductionmentioning
confidence: 99%